2008
DOI: 10.1002/cbf.1472
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNA‐binding proteins possibly involved in modulating human AT1 receptor mRNA stability

Abstract: Angiotensin II exerts its cardiovascular effects mainly through the activation of AT(1) receptors. These receptors can be regulated at a post-transcriptional level, that is through the modulation of the mRNA stability. This regulation usually involves proteins which are able to bind the 3'UTR of the mRNA molecule. The experiments of the present paper were performed in order to characterize the RNA-binding proteins interacting with the hAT(1) receptor mRNA in human vascular smooth muscle cells. Immunoblot analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a separate study, an elevated level of AT1R gene expression in the brainstem of spontaneously hypertensive rat was observed [37]. The transcriptional activity and mRNA stability of AT1R gene is regulated by specific RNA-binding proteins [38]. The role of AT1R protein expression in the regulation of blood pressure has been reported in recent studies [39][40].…”
Section: Introductionmentioning
confidence: 82%
“…In a separate study, an elevated level of AT1R gene expression in the brainstem of spontaneously hypertensive rat was observed [37]. The transcriptional activity and mRNA stability of AT1R gene is regulated by specific RNA-binding proteins [38]. The role of AT1R protein expression in the regulation of blood pressure has been reported in recent studies [39][40].…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, the AUF1 proteins have been shown to bind to and destabilize the mRNAs encoding human angiotensin 1 receptor (47), sarcoendoplasmic reticulum calcium ATPase2a (5), and the calcitonin receptor (69). Furthermore, HuR and AUF1 have common targets, and growing evidence has demonstrated that homomultimerization of HuR and AUF1 can bind simultaneously and competitively to a single ARE (32,47,69). Interestingly, both HuR and the AUF1 proteins target the ARE in the c-myc 3=-UTR (18,31).…”
mentioning
confidence: 85%
“…hnRNP A1 is a multifunctional protein that is implicated in diverse steps of RNA metabolism including splicing, 24 mRNA stability 25 and translation. 17 hnRNP A1 has been previously shown to bind several labile mRNAs that contain the AUUUA sequence, including the granulocyte-macrophage colony-stimulating factor (GM-CSF), 25 human angiotensin receptor AT 1 , 26 and cytochromes P450, 2A6 and 2A5. 27,28 A similar AUUUA sequence is found in ARE no.…”
Section: Discussionmentioning
confidence: 99%